The Crisis of Functionalism and the Reform of European Economic Governance (Politeja, 2015)
This paper studies the impact of the sovereign debt crisis on the development of the process of European integration and the constitutional framework of the EU. The first section focuses on the causes of the sovereign debt crisis, analysing the structural deficits and weaknesses of the Economic and Monetary Union (EMU). The second section looks at the reforms, which have been progressively adopted by the Eurozone to overcome the crisis and prevent the collapse of the single currency. The third section reflects on the longstanding contradictions of the integration process, in terms of its legitimacy and effectiveness, which the crisis has definitely highlighted demanding an effective solution. In this regard, the paper argues that the sovereign debt crisis represents a turning point in the history of European unification, marking the limits of the functionalist approach of integration and demanding a re‑launch of the constitutional project in order to provide the monetary union with a veritable economic government.